2023
DOI: 10.1017/s1478951523000780
|View full text |Cite
|
Sign up to set email alerts
|

Polarization in public attitudes toward end-of-life decisions in Israel – A cross-sectional study

Abstract: Objectives End-of-life (EoL) processes are a complex socio-normative and ethical phenomenon. This study aimed to generate a database of public opinion in Israel concerning EoL processes and decisions and to identify differences in attitudes across subgroups in the population, particularly based on experience as a family caregiver of a dying patient. Methods This cross-sectional study was performed in late March 2022. The study utilized an online sample of 605 adults over the age of 50 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 30 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…After removing 1572 duplicates, 7841 unique records were obtained and screened. We reviewed 167 full-text studies, of which 33 studies were finally included [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After removing 1572 duplicates, 7841 unique records were obtained and screened. We reviewed 167 full-text studies, of which 33 studies were finally included [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Search Resultsmentioning
confidence: 99%
“…Most of them were conducted at a national level, with the exception of 10 multinational ones [9,[12][13][14]44,45,48,49,57,59]. The individual national studies included four studies from France [5,17,19,50], three studies from the USA [10,16,56], two studies each from Turkey [8,43], China [46,47], and Brazil [42,53], as well as one study each from Israel [51], Croatia [11], South Africa [15], India [58], Italy [54], Portugal [52], Spain [7], Greece [6], Sweden [18], and Canada [55]. Four out of 10 multinational studies were conducted in Europe [9,44,48,49], one in Asia [57], one in Australia and New Zealand [12], one in the Middle East [59], one in both the US and Europe [45], and two on a global scale [13,14].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Study participants with prior personal involvement did not reveal attitudes that were fundamentally different from those expressed by the general public. Furthermore, we were surprised by the low-magnitude associations between sociodemographic variables and attitudes toward euthanasia and withdrawal of life-prolonging treatment, in contrast to findings in other studies that have shown associations with variables such as age, educational level, sex, income level, religiosity, or health-related factors with certain attitudes toward euthanasia, withdrawal of life-prolonging treatment, and end-of-life decision-making . We assumed that, in a culturally diverse society, personal views become less determined by sociodemographic variables than in the past.…”
Section: Discussionmentioning
confidence: 99%